Forensic Victimology and Femi(ni)cide: A Transdisciplinary Approach on Forensic Evidence and its Contexts (Volume II) - Cortes-Perez, Oscar Ivan (Springer Nature Switzerland, 2024)
part i. social and behavioral forensic investigation in femi(ni)cide -- 1. investigative and forensic interview: estandards of practice in feminicide contexts -- 2. forensic discussion and formulation: ecological-intersectional perspectives in victimology and criminology to understand feminicide -- 3. forensic psychopathological aspects of femicidal offenders: an analysis of insanity and imputability -- 4. criminal motivations in femicide -- 5. motivations for juvenile offending behaviour and femicide -- 6. criminal profiling in femicide -- 7. forensic psychological evaluation of survivors of feminicide, a dignified forensic intervention for victims -- 8. forensic victimology and context analysis: the ecological-intersectional dimensions model on the victimization context -- 9. the use of applied victimology to increase solvability for femicide -- part 2. final reflections: truth, memory and justice for victims and survivors of femi(ni)cide -- 10. truth, memory, therapeutical and social justice: towards a victimology ‘about’ victims, ‘for’ victims and ‘along with’ victims aof femi(ni)cide.